Classification of nuclear NPP reactors - Yefimov, Olexander Vyacheslavovych; Tiutiunyk, Larysa Ivanivna; Kavertsev, Valery Leonidovich; Harkusha, Tetyana Anatoliivna; Sydorkin, Igor Dmytrovych (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article deals with the classification of NPP nuclear reactors. A nuclear reactor is a device in which a chain reaction of nuclear fission of heavy elements uranium, plutonium, and thorium takes place, which controls and maintains itself. The possibility of such a reaction is ensured by the fact that each act of nuclear fission produces two or three neutrons capable of causing the fission of other nuclear fuel nuclei loaded into the reactor. In the reactor, simultaneously with the nuclear fission process, there is always, firstly, the absorption of neutrons by materials located in the active zone, and, secondly, the outflow of neutrons from the active zone of the reactor. These two factors make it possible to regulate the nuclear fission process so that the number of neutrons in the active zone and the number of acts of fission per unit of time are constant. Nuclear reactors are very diverse in terms of their parameters, purpose, design and a number of other features. Nuclear reactors can be classified according to the following main distinguishing features: the amount of neutron energy that causes nuclear fission; by type of retarder; according to the type and parameters of the coolant; by constructive execution; according to the compositional decision; by appointment. At nuclear power plants, nuclear reactors are used to generate electrical and thermal energy. At nuclear power plants, they are used to generate thermal energy for the purpose of heating and industrial heat supply. In ship power plants, they are used as sources of thermal, mechanical and electrical energy.

У матеріалах статті розглядається класифікація ядерних реакторів АЕС. Ядерний реактор являє собою пристрій, в якому здійснюється ланцюгова реакція поділу ядер важких елементів урану, плутонію, торію, яка сама себе контролює і підтримує. Можливість здійснення такої реакції забезпечується тим, що кожен акт поділу ядра виробляє два або три нейтрони, здатних викликати поділ інших ядер ядерного палива, завантаженого в реактор. У реакторі одночасно з процесом поділу ядер завжди відбувається, по-перше, поглинання нейтронів матеріалами, що знаходяться в активній зоні, і, по-друге, витікання нейтронів з активної зони реактора. Ці два чинники дають можливість регулювати процес поділу ядер так, щоб число нейтронів в активній зоні і число актів поділу в одиницю часу були постійними. Ядерні реактори за своїми параметрами, призначенням, конструктивним виконанням і за рядом інших ознак дуже різноманітні. Класифікувати ядерні реактори можна за такими основними відмінними ознаками: за величиною енергії нейтронів, що викликають поділ ядер; за видом сповільнювача; за видом і параметрами теплоносія; за конструктивним виконанням; за компонувальним рішенням; за призначенням. На атомних електростанціях ядерні реактори застосовуються для вироблення електричної і теплової енергій. На атомних станціях теплопостачання вони використовуються для вироблення теплової енергії з метою опалювання і промислового теплопостачання. У суднових енергетичних установках вони застосовуються як джерела теплової, механічної і електричної енергій.
Класифікація ядерних реакторів АЕС
Keywords: nuclear power plants; active zone; nuclear reactor; атомні електричні станції; активна зона; ядерний реактор